Expression of DNMT1 and DNMT3a are regulated by GLI1 in human pancreatic cancer. - ShanShan He; Feng Wang; LiJuan Yang; ChuanYong Guo; Rong Wan; AiWu Ke; Ling Xu; GuoYong Hu; XuanFu Xu; Jie Shen; XingPeng Wang (PLoS ONE, 2011)
GLI1, as an indispensable transcriptional factor of Hedgehog signaling pathway, plays an important role in the development of pancreatic cancer (PC). DNA methyltransferases (DNMTs) mediate the methylation of quantity of tumor-related genes. Our study aimed to explore the relationship between GLI1 and DNMTs.Expressions of GLI1 and DNMTs were detected in tumor and adjacent normal tissues of PC patients by immunohistochemistry (IHC). PANC-1 cells were treated by cyclopamine and GLI1-siRNA, while BxPC-3 cells were transfected with overexpression-GLI1 lentiviral vector. Then GLI1 and DNMTs expression were analyzed by qRT-PCR and western blot (WB). Then we took chromatin immunoprecipitation (ChIP) to demonstrate GLI1 bind to DNMT1. Finally, nested MSP was taken to valuate the methylation levels of APC and hMLH1, when GLI1 expression altered.IHC result suggested the expressions of GLI1, DNMT1 and DNMT3a in PC tissues were all higher than those in adjacent normal tissues (p<0.05). After GLI1 expression repressed by cyclopamine in mRNA and protein level (down-regulation 88.1±2.2%, 86.4±2.2%, respectively), DNMT1 and DNMT3a mRNA and protein level decreased by 91.6%±2.2% and 83.8±4.8%, 87.4±2.7% and 84.4±1.3%, respectively. When further knocked down the expression of GLI1 by siRNA (mRNA decreased by 88.6±2.1%, protein decreased by 63.5±4.5%), DNMT1 and DNMT3a mRNA decreased by 80.9±2.3% and 78.6±3.8% and protein decreased by 64.8±2.8% and 67.5±5.6%, respectively. Over-expression of GLI1 by GLI1 gene transfection (mRNA increased by 655.5±85.9%, and protein increased by 272.3±14.4%.), DNMT1 and DNMT3a mRNA and protein increased by 293.0±14.8% and 578.3±58.5%, 143.5±17.4% and 214.0±18.9%, respectively. ChIP assays showed GLI1 protein bound to DNMT1 but not to DNMT3a. Results of nested MSP demonstrated GLI1 expression affected the DNA methylation level of APC but not hMLH1 in PC.DNMT1 and DNMT3a are regulated by GLI1 in PC, and DNMT1 is its direct target gene.